Self Efficacy dan Profesionalisme Sebagai Variabel Intervening Antara On The Job Training Dan Kinerja Pegawai - Marghareta, Leoni; Damarwulan, Liza Mumtazah (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2021)
This study was conducted with the aim of knowing the extent to which on the job training methods can affect employee performance and whether the intervening variables of professionalism and self efficacy can increase the effect of on the job training methods on employee performance. Total population and sample are 74 respondents. The data analysis technique of this research uses Partial Least Square (SmartPLS 3.0). The results obtained are on the job training affects employee performance by 22.9%, on the job training affects professionalism is 72.7%., on the job training affects self-efficacy by 77.4%, professionalism affects performance employees by 44.7% and self-efficacy affects employee performance by 32.7%. As well as the value of the indirect effect between on the job training, Professionalism and Employee Performance, the original sample interval coefficient value is 0.325 or 34.5% while the indirect effect between on the job training, Self efficacy and Employee Performance is obtained by the original sample interval coefficient value of 0.253 or 25.3%.